Integrating dictionary on taxation accounting terminology as self-learning kit in English for specific purposes - Handayani, Luh Nyoman Chandra; Sukerti, Gusti Nyoman Ayu; Wicaksana, Ketut Arya Bayu (Politeknik Negeri Bali, 2022)
Specialized tax and accounting dictionaries are useful for vocational students as an independent learning medium, as they facilitate vocabulary mastery and eliminate the need for general dictionary lookups. The focus of this paper is the development of a dictionary of tax accounting terminology as an independent learning medium in the academic reading process and analysis of its implementation. This learning medium was developed using an adaptation of the ADDIE model which consists of five phases: needs analysis, design, development, implementation, and evaluation. This study elaborates on the student's perspective on the product produced in this study, namely a self-learning kit in the form of a tax accounting terms dictionary as well as student experiences in using dictionary applications to support their learning. The dictionary covers 731 data entries with the description of word translation, word class, definition, and sample sentences in English and Indonesian. In addition, users are also provided with 8 self-evaluation exercises in Quizizz which can be accessed via barcode scanning or link. Data analysis in the form of respondents’ responses in Google Form was described based on aspects of student feedback after using the dictionary. The descriptions of student perceptions are summarized into aspects of design, content, and usability. Students gave positive responses in those three aspects and highlighted that the dictionary assisted them in improving their vocabulary mastery, and reading comprehension as well as in reflecting on their learning progress through self-evaluation.